Clinical implications for dopaminergic and functional neuroimage research in cognitive symptoms of Parkinson's disease - Shigeki Hirano (BMC, 2021)
Abstract Evidence from dopaminergic image and cerebral blood flow/metabolism images have shed light on symptomatology of cognitive aspects in brain physiology of healthy human as well as patients with Parkinson's disease. Cognitive impairment in Parkinson's disease is characterized by executive, visuospatial, attentional disturbances. Dopaminergic system includes triadic parallel pathways. The mesostriatal pathway consist of posterolateral putamen and motor areas, the mesocortical pathway of dorsal caudate nucleus and dorsolateral prefrontal cortex, and the mesolimbic pathway of ventral striatum, anterior cingulate cortex. The mesocortical pathway is responsible for the executive function which may change by administration of dopaminergic medication. The mesolimbic pathway is associated with motivation and reward prediction which may result in depression or apathy when dopamine level was suboptimal, impulse control disorder and punding when dopamine was over the optimal level. Abnormal brain metabolism/perfusion related to cognitive impairment in Parkinson's disease are relatively reduced activity located in frontal and parietal association areas and relatively increased activity in the cerebellum. In the anterior brain, the mesocortical pathway, is responsible for verbal memory and executive function, which originates with caudate dopaminergic system and account for mild cognitive impairment of Parkinson's disease. The posterior brain system which includes the parietal, temporal, and occipital cortices, is responsible for the memory and visuospatial function, and related to cholinergic dysfunction and possibly glucocerebrosidase gene variants, relating to dementia in Parkinson's disease. The role of cerebellum in Parkinson's disease remains unclear but emerging evidence suggests that it may relate to the sequencing detection and affective symptoms. The dual syndrome hypothesis is helpful for understanding the mechanism of cognitive impairment in Parkinson's disease and optimal symptom management.